CRIMINAL LAW ENFORCEMENT POLICY ON MINERAL AND COAL MINING BUSINESSES - Andre Birawa; Liliana Tedjosaputro (PSHPM Untag Semarang, 2020)
The implementation of the criminal law enforcement policy on mineral and coal mining businesses (minerba) still occurs several violations of Article 158 of the Law of the Republic of Indonesia No 4 of 2009 (minerba Law). This journal aims to find out and analyze: 1) criminal law policy in law enforcement on illegal mining businesses according to the Minerba Law, and 2) current law enforcement constraints and future improvements. The normative juridical research approach places secondary data, in the form of primary legal material (Minerba Law) as the main material. Meanwhile, primary data acts as supporting analysis, which is obtained using interview techniques. Secondary data was obtained through the study of legal literature, especially Case No. 237 / Pid. Sus / 2018 / PN Jpa. The entire dawas ta was analyzed using descriptive qualitative methods. Results: (1) Minerba Act, qualified as administrative criminal law. The criminal provisions are regulated in 8 articles with the threat of imprisonment, confinement and fines. (2) Law enforcement constraints from the Legal Substance dimension is the equalization of all mining activity permits in the form of Mining Business Permits. The legal structure perspective, demands large funding requirements. Internal Legal Culture experiences obstacles in coordination between Police investigators and PPNS. Externally, it explains that people prioritize economic value. In the future, a Rock Mining Permit is required, consistency in the application of article 158 and solid coordination between police and ESDM investigators, as well as education on environmental values.